The EBMT Handbook Hematopoietic Stem Cell Transplantation and Cellular Therapies - Carreras, Enric; Dufour, Carlo; Mohty, Mohamad; Kröger, Nicolaus (Springer Nature, 2019)
This Open Access edition of the European Society for Blood and Marrow Transplantation (EBMT) handbook addresses the latest developments and innovations in hematopoietic stem cell transplantation and cellular therapy. Consisting of 93 chapters, it has been written by 175 leading experts in the field. Discussing all types of stem cell and bone marrow transplantation, including haplo-identical stem cell and cord blood transplantation, it also covers the indications for transplantation, the management of early and late complications as well as the new and rapidly evolving field of cellular therapies. This book provides an unparalleled description of current practices to enhance readers' knowledge and practice skills.